Assessment of snake DNA barcodes based on mitochondrial COI and Cytb genes revealed multiple putative cryptic species in Thailand - Laopichienpong, Nararat; Muangmai, Narongrit; Supikamolseni, Arrjaree; Twilprawat, Panupon; Chanhome, Lawan; Suntrarachun, Sunutcha; Peyachoknagul, Surin; Srikulnath, Kornsorn (Gene, 2016)
DNA barcodes of mitochondrial cytochrome c oxidase I (COI), cytochrome b (Cytb) genes, and their combined data sets were constructed from 35 snake species in Thailand. No barcoding gap was detected in either of the two genes from the observed intra- and interspecific sequence divergences. Intra- and interspecific sequence divergences of the COI gene differed 14 times, with barcode cut-off scores ranging over 2%–4% for threshold values differentiated among most of the different species; the Cytb gene differed 6 times with cut-off scores ranging over 2%–6%. Thirty-five specific nucleotide mutations were also found at interspecific level in the COI gene, identifying 18 snake species, but no specific nucleotide mutation was observed for Cytb in any single species. This suggests that COI barcoding was a better marker than Cytb. Phylogenetic clustering analysis indicated that most species were represented by monophyletic clusters, suggesting that these snake species could be clearly differentiated using COI barcodes. However, the two-marker combination of both COI and Cytb was more effective, differentiating snake species by over 2%–4%, and reducing species numbers in the overlap value between intra- and interspecific divergences. Three species delimitation algorithms (general mixed Yule-coalescent, automatic barcoding gap detection, and statistical parsimony network analysis) were extensively applied to a wide range of snakes based on both barcodes. This revealed cryptic diversity for eleven snake species in Thailand. In addition, eleven accessions from the database previously grouped under the same species were represented at different species level, suggesting either high genetic diversity, or the misidentification of these sequences in the database as a consequence of cryptic species. •The COI barcode and Cytb barcode cut-off scores for over 25 snake species in Thailand are proposed for species identification.•Two-marker combination of both COI and Cytb is conducted to differentiate snake species.•Three species delimitation algorithms are performed to reveal multiple putative cryptic species.